1992
DOI: 10.1128/aac.36.4.733
|View full text |Cite
|
Sign up to set email alerts
|

(-)-2'-deoxy-3'-thiacytidine is a potent, highly selective inhibitor of human immunodeficiency virus type 1 and type 2 replication in vitro

Abstract: The (-)-enantiomer of 2'-deoxy-3'-thiacytidine (3TC) was found to be a potent and selective inhibitor of human immunodeficiency virus types 1 (HIV-1) and 2 (HIV-2) in vitro. We determined its antiviral activity against a number of laboratory strains of HIV-1 and HIV-2 in a range of CD4-bearing lymphocyte cell lines (mean 50% inhibitory concentration [IC50] range, 4 nM to 0.67 microM). 3TC was also active against a range of HIV-1 strains in peripheral blood lymphocytes (mean IC50 range, 2.5 to 90 nM). The IC50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
107
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(108 citation statements)
references
References 27 publications
0
107
1
Order By: Relevance
“…5B). To determine whether HIV replication was necessary for decreased IL-21 production, we infected PBMCs with and without 3TC; a nucleoside reverse transcriptase inhibitor known to block viral replication (31). The treatment with 3TC restored IL-21 production in the cell culture supernatants (p , 0.01) as well as + T cells were isolated from human PBMCs after 72 h activation with PHA (10 mg/ml) and IL-2 (100 U/ml).…”
Section: Hiv Infection Decreases the Ability Of Human Cd4 + T Cells Tmentioning
confidence: 99%
“…5B). To determine whether HIV replication was necessary for decreased IL-21 production, we infected PBMCs with and without 3TC; a nucleoside reverse transcriptase inhibitor known to block viral replication (31). The treatment with 3TC restored IL-21 production in the cell culture supernatants (p , 0.01) as well as + T cells were isolated from human PBMCs after 72 h activation with PHA (10 mg/ml) and IL-2 (100 U/ml).…”
Section: Hiv Infection Decreases the Ability Of Human Cd4 + T Cells Tmentioning
confidence: 99%
“…The use of the nucleoside analog RT inhibitor (Ϫ)2Ј,3Ј-dideoxy-3Ј-thiacytidine (3TC) imposes strong selection for a single amino acid substitution in the conserved Tyr-Met-Asp-Asp motif of the catalytic site of RT. High-level resistance is typically conferred by amino acid substitutions that change the methionine at position 184 to isoleucine (M184I), valine (M184V), or threonine (M184T) (3,4). When 3TC is used as a single drug for people infected with HIV-1, drug-resistant virus outcompetes wild-type virus within a few weeks (3), suggesting that the required sequence changes commonly preexist in the virus population.…”
mentioning
confidence: 99%
“…39) Indeed, the L-isomer of lamivudine was more potent and less cytotoxic than its D-isomer. [40][41][42][43] We concluded that our synthetic approach was effective. Adopting a similar synthetic scheme for the D-isomers depicted above, we were able to obtain L-4′-thioarabinonucleosides from D-xylose by shifting the chiral carbons employed.…”
Section: Synthesis Of L-isomers Of 4′-thionucleosidesmentioning
confidence: 88%